Improving Conservative Treatment for Adhesive Tubohepatitis - Erkinboy o'g'li, Qosimov Mirkamol; A. A., Khayitov (Journal of Science in Medicine and Life, 2025)
Eustachitis is an inflammation of the mucous membrane of the auditory tube. It can be acute and chronic, unilateral and bilateral. Some researchers believe that damage to the auditory tube alone is almost impossible: the middle ear, that is, the auditory tube, the tympanic cavity and the mastoid process are usually involved in the inflammatory process in one way or another. Due to this combination, eustachitis is also called secretory (exudative) otitis media. Other synonyms: tubo-otitis, salpingo-otitis, otosalpingitis, catarrh of the eustachian tube and tubotympanitis [11]. Eustachitis occurs in people of any age, but is more common in children, since their auditory tube is shorter and wider.